Antibiotics re-booted—time to kick back against drug resistance - Mark A. T. Blaskovich; Matthew A. Cooper (npj Antimicrobials and Resistance)
Abstract After decades of neglect and a decline in antibiotic research and development, we are now finally witnessing the advent of new funding programs dedicated to new therapies. In addition to traditional new chemical entities that directly kill or arrest the growth of bacteria, alternative approaches are being identified and advanced towards proof-of-concept trials in the clinic. We briefly review the current pipeline of conventional new antibiotics and highlight in more depth promising alternatives, including potentiators of antibiotic action, bacteriophage, lysins and microbiome modulation. More innovative approaches, such as adaptive and innate immune modulators, CRISPR-Cas and diagnostic guided ‘theranostics’ are discussed and contrasted. Such exploratory therapies may require the development of alternative regulatory and clinical development pathways, but represent a potential circuit breaker from the current ‘arms race’ between bacteria and traditional antibiotics.